The Influence of Digital Marketing and Consumer Behavior on Consumer Product Purchases Among Older Consumers: A Systematic Review and Meta Analytic Evidence Synthesis - Sri Yulianti; Ignatius Erik Sapta Yanuar; Sakti Brata Ismaya (Pelopor Publikasi Akademika, 2026)
Digital marketing has transformed consumer purchasing behavior, including among older consumers who increasingly engage with e-commerce, social media platforms, and personalized advertising. However, evidence regarding its influence on older consumers’ purchase decisions remains fragmented. This systematic review and meta-analytic evidence synthesis evaluated the association between digital marketing exposure, consumer behavior mechanisms, and purchase decisions among consumers aged 50 years and older. Following the PRISMA 2020 guidelines and PICOS framework, Scopus, EBSCOhost, Google Scholar, and Taylor & Francis Online were searched for studies published between 2010 and 2025 that examined older consumers, digital marketing variables, and purchase outcomes. Methodological quality was appraised using the Mixed Methods Appraisal Tool (MMAT) and adapted risk-of-bias domains. Due to inconsistently reported effect sizes, the findings were synthesized narratively as a meta-analysis-ready evidence synthesis. The evidence consistently indicated positive associations between digital marketing, consumer trust, perceived usefulness, digital literacy, online engagement, and older consumers’ purchase decisions. Social media advertising, personalized advertising, e-commerce convenience, online trust, and perceived ease of use emerged as the most frequently reported mechanisms influencing purchase behavior. The certainty of evidence was moderate for trust and perceived usefulness, low-to-moderate for digital literacy and personalization, and low for channel-specific comparative effectiveness. Digital marketing positively influenced older consumers’ purchase decisions when strategies were trustworthy, accessible, personalized, and aligned with older adults’ digital capabilities. Future research should report extractable effect sizes, employ longitudinal designs, and examine age cohort, digital literacy, product category, platform type, and cultural context as potential moderators.